MURABAHAH FINANCING PROBLEM SOLVING STRATEGIES: ANALYSIS AND EVALUATION - Haris al Amin; Syawal Harianto; Abi Waqqosh; Abdul Halim (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
The research was conducted wtith the aim of analyzing the settlement of troubled murabahah financing at BPRS Rahmah Hijrah Agung Lhokseumawe. This research is a type of field research conducted in BPRS to obtain relevant data or data sources (primary and secondary) the author conducts data collection through observation, documentation and interviews. Then the data obtained were analyzed using descriptive methods. Based on the research and discussion that the author has done, it can be concluded that the factors that cause problematic murabahah financing can be caused by bank who are not careful in analyzing financing and lack of supervision after funding is given in addition it is also caused by customers who intentionally do not want to fulfill their obligations or because the customer’s business has decreased. The handling of murabahah financing is problematic in the BPRS Rahmah Hijrah Agung Lhokseumawe, namely by collecting incentives, granting warning letters or reprimand, extension of the installment period and execution of collateral. Settlement of troubled financing carried. Out by BPRS Rahmah Hijrah Agung Lhokseumawe is not contrary to islamic because in accordance with the fatwa of the national shariah council of the Indonesia ulama council in handling troubled financing BPRS provides time allowance for customers who have not been able to pay their obligations by giving an ectended period of time to pay installments for customers who fall into the category of experiencing a disaster or a business downturn but still be saved.